CEAP's influence on the management practices of selected member schools - Aguiling, Maria Adiel Hular (2008)
The Catholic Educational Association of the Philippines (CEAP) to some extent influences the management practices of its member schools as perceived by the administrators and teachers. A cross sectional research design was used employing semi-structured interviews and self-completion questionnaires. Eight administrators and one hundred teachers from seven CEAP member schools in the National Capital Region were selected through simple random sampling. Findings showed that both administrators and teachers agree that CEAP has influence over many management practices of its school. The study also revealed that the CEAP member schools practice to a high degree the management functions of planning, organizing, leading and controlling.